1971
DOI: 10.1111/j.1476-5381.1971.tb07205.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antinociceptive activities of physostigmine, oxotremorine and morphine in the mouse

Abstract: Summary1. Morphine, oxotremorine and physostigmine showed antinociceptive activity in mice using the hot plate reaction time test. 2. The action of morphine, but not that of oxotremorine, was antagonized by naloxone and by nalorphine, whereas the effect of physostigmine was unaffected by naloxone and increased by nalorphine.3. The antinociceptive effects of morphine and of physostigmine were increased by procedures reported to increase the ratio of 5-hydroxytryptamine to dopamine in the brain. It was decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Within rodents (rats and mice), out of a total of 30 observations of different cholinergic agents, 21 (i.e., about two-thirds) of the studies show positive analgesic effect. The nine negative results, however, include two studies using neostigmine (Saxena, 1958;Pleuvy and Tobias, 1971; on rats and mice, respectively) and another negative study by Kamat et ai., (1972) using intraperitoneal administration of carbachol in mice. Neither neostigmine nor carbachol cross the blood brain barrier when administered parenterally and their lack of effect may merely indicate that peripheral cholinergic mechanisms do not playa role in nociception.…”
Section: Species Differencesmentioning
confidence: 90%
“…Within rodents (rats and mice), out of a total of 30 observations of different cholinergic agents, 21 (i.e., about two-thirds) of the studies show positive analgesic effect. The nine negative results, however, include two studies using neostigmine (Saxena, 1958;Pleuvy and Tobias, 1971; on rats and mice, respectively) and another negative study by Kamat et ai., (1972) using intraperitoneal administration of carbachol in mice. Neither neostigmine nor carbachol cross the blood brain barrier when administered parenterally and their lack of effect may merely indicate that peripheral cholinergic mechanisms do not playa role in nociception.…”
Section: Species Differencesmentioning
confidence: 90%
“…All the more so when it is borne in mind that centrally-acting cholinomimetic drugs have potent analgesic activity (George et al, 1962;Pleuvry & Tobias, 1971;Bartolini et al, 1980) …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that muscarinic cho linergic receptors may be involved in induc tion of analgesia [39], Also a synergistic ac tion between choline and morphine has been demonstrated [4,16]. Other investigators have suggested that central cholinergic mechanisms are involved in analgesia in duced by morphine [8,29], It has also been reported that morphine analgesia may be due either to a direct effect on an opiate receptor [26] or its possible role as a musca rinic agonist [8], More recently, a striking correspondence between striatal islands of closely packed opiate receptors and acetyl cholinesterase zones has been reported [15]. Also the acute administration of morphine has been found to be associated with inhibi tion of ACh release [1,19,24] and the decline in ACh turnover rate [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a toxic sy nergism between choline and morphine was demonstrated [ 16], It has also been suggested that central cholinergic mechanisms are in volved in morphine-induced analgesia [8,29]. Recently, we have found that the central cholinergic system is related to the rapid development of tolerance to ethanol [34], One possible mechanism by which morphine and related narcotic agonists elevate brain acetylcholine [31] could be related to the inhibition of acetylcholine (ACh) release from central cholinergic neurons [19].…”
Section: Introductionmentioning
confidence: 99%